The Application of Stochastic Order to Stochastic Multiobjective Programming Problems - Zheng, Ming Fa; Wang, Zu Tong; He, Qi Hang; Su, Dong Qing (Applied Mechanics and Materials, 2014)
This paper is devoted to the application of stochastic order to the with stochastic multiobjective programming problem. A new method, called stochastic approach, is originally presented based on stochastic order. The partial Pareto efficient solution is defined first, and then several types of stochastic order from the viewpoint of practical problems are proposed. The results obtained can provide theoretical basis for dealing with the stochastic problems in field of civil engineering and transportation.